Land use and land cover changes in São Paulo Macro Metropolis and implications for water resilience under climate change (Sustainability in Debate, 2021)
The São Paulo Macro Metropolis (MMP) is a geographical arrangement that brings together the most significant Brazilian socioeconomic figures and faces numerous challenges, such as heavy pressure on natural resources. Through compilation, spatialization and cross-referencing of data, this work assessed time series of land use and land cover of the last decades, the water supply status in an urban environment and climate data projection for MMP. Municipalities with different profiles were identified: those with positive final balances and those with negative final balances about the maintenance of their natural areas. Furthermore, more than half of the municipalities of the MMP have low water supply assurance, which can be aggravated due to climate change, as predicted in several climate models. The characterization of municipalities based on this information allowed identifying which of them are the most vulnerable, and these results indicate paths for coordinated actions at local and regional levels to increase water resilience in the macro-region.